Meraih Hikmah, Menemukan Makna: Intervensi Melalui Psikoedukasi untuk Meningkatkan Kebermaknaan Hidup di Pesantren Lansia Ahsanu ‘Amala: Finding Wisdom, Discovering Meaning: A Psychoeducational Intervention to Enhance Meaning in Life at Pesantren Lansia Ahsanu’ Amala - Putri, Syifa Amalia; Hananto, Nabila Fitri Ayu; Ramdan, M. Raihan Khoirul; Azzahro, Nella Apriliani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Older people often experience physical, social, and emotional changes that affect their psychological well-being. These changes can lead to feelings of loneliness, alienation, and a decreased ability to find meaning in life. This condition indicates the need for interventions that help older adults enhance self-acceptance, gratitude, and inner peace in later life. This program aims to strengthen their sense of meaning in life through spirituality-based psychoeducation conducted in an elderly pesantren setting. The program was implemented in three stages: initial assessment, intervention, and evaluation involving twenty-seven participants at Pesantren Lansia Ahsanu Amala. The initial assessment included observations, group discussions, and questionnaire administration to identify emotional needs and baseline levels of meaning in life. The intervention consisted of two psychoeducation sessions focusing on reflection on past experiences and on understanding life meaning from a spiritual perspective, combined with reflective exercises and interactive discussions. The evaluation was carried out by comparing pre-test and post-test results and by observing participant engagement throughout the activities. The findings showed an increase in participants' understanding of life meaning, indicated by their improved ability to reflect on past experiences more positively, to understand meaning in life from an Islamic perspective, and to develop self-acceptance. The program also strengthened social connections and fostered a more stable emotional atmosphere among participants.